Chronic lung disease in HIV-infected children established on antiretroviral therapy - Rylance, J; Mchugh, G; Metcalfe, J; Mujuru, H; Nathoo, K; Wilmore, S; Rowland-Jones, S; Majonga, E; Kranzer, K; Ferrand, R (Lippincott, Williams & Wilkins, 2016)
Respiratory disease is a major cause of morbidity and mortality in HIV-infected children. Despite antiretroviral therapy (ART), children suffer chronic symptoms. We investigated symptom prevalence, lung function, and exercise capacity among older children established on ART, and an age-matched HIV-uninfected group.A cross-sectional study in Zimbabwe of: 1) HIV-infected children aged 6-16 years receiving ART for over six months; 2) HIV-uninfected children attending primary health clinics from the same area.Standardised questionnaire, spirometry, Incremental Shuttle Walk Testing (ISWT), CD4 count, HIV viral load, and sputum culture for tuberculosis were performed.202 HIV-infected and 150 uninfected participants (median age 11.1 years in each group) were recruited. Median age at HIV diagnosis and ART initiation was 5.5 (IQR 2.8-7.5) and 6.1 years (IQR 3.6-8.4) respectively. Median CD4 count was 726 cells/μl, and 79% had HIV viral load<400copies/ml. Chronic respiratory symptoms were rare in HIV-uninfected children (n = 1 [0.7%]), but common in HIV-infected participants (51 [25%]), especially cough (30 [15%]) and dyspnoea (30 [15%]). HIV-infected participants were more commonly previously treated for tuberculosis (76 [38%] versus 1 [0.7%], p < 0.001), had lower exercise capacity (mean ISWT distance 771m versus 889m respectively, p < 0.001), and more frequently abnormal spirometry (43 [24.3%] versus 15 [11.5%], p = 0.003) compared to HIV-uninfected participants. HIV diagnosis at an older age was associated with lung function abnormality (p = 0.025). No participant tested positive for M. tuberculosis.In children, despite ART, HIV is associated with significant respiratory symptoms and functional impairment. Understanding pathogenesis is key, as new treatment strategies are urgently required.